Controversies in globalization : contending approaches to international relations - Haas, Peter M. (ed.); Hird, John A. (ed.); Mcbrantney, Beth (ed.) (Washington D.C, 2010)
Most instructors agree that debate-style readers can be effective and provocative teaching tools in the classroom. But if the readings are not in dialogue with one another, the crux of the debate is lost on students, and the reader fails to add real depth to the course.Controversies in Globalization solves this issue by inviting 15 pairs of scholars and practitioners to write specifically for the volume, directly addressing current and relevant questions in international relations through brief &BAD:ldquo;yes&BAD:rdquo; and &BAD:ldquo;no&BAD:rdquo; pieces. Providing students with necessary context, the editors offer introductions that effectively frame the debate and make clear what is at stake, both from a theoretical as well as from a practical perspective. Concluding discussion questions in each chapter encourage critical thinking and analysis.
Keywords: Globalization